THE MEDIATING ROLE OF ELECTRONIC WORD OF MOUTH IN THE RELATIONSHIP BETWEEN CONTENT MARKETING AND PURCHASE DECISIONS ON TIKTOK SHOP - Rustianah Rustianah; Nur'Aeni Nur'Aeni; 3Riski Eko Ardianto; Wiyarno Wiyarno; Lisa Sri Kartika (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2026)
PURPOSE - This study aims to analyze the influence of content marketing on purchase decisions and to test the role of E-WOM as a mediating variable in this relationship among TikTok Shop users. Conceptually, this study employs the Stimulus–Organism–Response (SOR) framework, positioning content marketing as the stimulus, E-WOM as the socio-psychological mechanism, and purchase decisions as the behavioral response.METHODOLOGY - The research method used is a quantitative approach with an explanatory design. Data were collected via an online questionnaire administered to TikTok Shop users selected using purposive sampling, with 100 respondents. Data analysis was conducted using SEM-PLS with the assistance of SmartPLS software to test direct and indirect relationships among variablesFINDING - The results revealed that content marketing significantly influenced purchase decisions (β = 0.265, p = 0.006) and E-WOM (β = 0.595, < 0.001). Furthermore, E-WOM significantly influenced purchase decisions (β = 0.561, p < 0.001). Regarding indirect relationships, E-WOM significantly mediated the relationship between content marketing and purchase decisions, with an indirect effect coefficient of β = 0.334 (p < 0.001). These findings indicate that E-WOM strengthens the influence of content marketing on purchase decisions among TikTok Shop users